Redescription of the sun-spider Mummucina titschacki Roewer, 1934 (Solifugae, Mummuciidae) with notes on the taxonomy of the genus - Botero-Trujillo, Ricardo (Zootaxa, 2014)
Mummucina Roewer, 1934 is the second largest genus in the South American sun-spider family Mummuciidae. The limits of this and other genera are largely unexplored, and the traditional classification system is controversial. In the present contribution, the type species Mummucina titschacki Roewer, 1934 is redescribed, aided by scanning electron micrographs and the examination of a series of 72 specimens (including males) from the type locality in Ecuador. Some taxonomic remarks are made.